2007
DOI: 10.4049/jimmunol.178.3.1748
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin, an Adipocytokine with Proinflammatory and Immunomodulating Properties

Abstract: Adipocytokines are mainly adipocyte-derived cytokines regulating metabolism and as such are key regulators of insulin resistance. Some adipocytokines such as adiponectin and leptin affect immune and inflammatory functions. Visfatin (pre-B cell colony-enhancing factor) has recently been identified as a new adipocytokine affecting insulin resistance by binding to the insulin receptor. In this study, we show that recombinant visfatin activates human leukocytes and induces cytokine production. In CD14+ monocytes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

44
735
5
49

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 830 publications
(852 citation statements)
references
References 66 publications
44
735
5
49
Order By: Relevance
“…When administered to mice, visfatin had similar effects on proinflammatory cytokine levels, especially increasing circulating IL-6 [18,19]. Furthermore, Li et al [20] demonstrated that visfatin affects macrophage function and IL-6 production.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…When administered to mice, visfatin had similar effects on proinflammatory cytokine levels, especially increasing circulating IL-6 [18,19]. Furthermore, Li et al [20] demonstrated that visfatin affects macrophage function and IL-6 production.…”
Section: Discussionmentioning
confidence: 96%
“…A number of reports concerning the proinflammatory effects of visfatin have shown that it dose-dependently upregulates the production of IL-1α, IL-6, and TNF-α in human monocytes [18,19]. When administered to mice, visfatin had similar effects on proinflammatory cytokine levels, especially increasing circulating IL-6 [18,19].…”
Section: Discussionmentioning
confidence: 97%
“…Since eNAMPT has been implicated in the regulation of inflammatory responses [15,[41][42][43], and since MPN-associated myelofibrosis has been interpreted as an inflammatory disease with uncontrolled myeloproliferation and cytokine secretion [7], we investigated the additional role of eNAMPT as an inflammatory cytokine. For this endeavor, we correlated eNAMPT levels to the marker of general inflammation, that is, plasma level of hs-CRP.…”
Section: Discussionmentioning
confidence: 99%
“…From an intracellular standpoint, visfatin is a dimeric type II phosphoribosyltransferase that serves a critical role as the rate-limiting step in the biosynthesis of NAD from nicotinomide and regulates the activity of NAD-dependent deacetylase Sirt1 in mammalian cells (30). On the other hand, visfatin appears to play an important role as a cytokine, secreted extracellularly in response to inflammatory stimuli such as lipopolysaccharide, TNF-␣, IL-1␤, and IL-6, capable of modulating the innate immune response in states of systemic inflammation and sepsis (6,15). Indeed, elegant experiments by Jia and colleagues (6), clearly demonstrate that visfatin is upregulated in neutrophils and macrophages, by proinflammatory stimuli of both host and microbial origin, and that it plays an essential role in inhibiting neutrophil apoptosis.…”
Section: Discussionmentioning
confidence: 99%